The Effect of Product Quality, Price on Purchasing Decisions on The Marketplace - Defin Shahrial Putra; Abdurrahim; Teguh Wicaksono; Mursanto (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
This study aims to determine product quality and price in purchasing decisions. This is because of the current digital era, the development of technology and information is running very rapidly, resulting in increasingly fierce business competition. In the business world, product quality and product price can stimulate a market response. The population in this study was 1230 people, with the sampling technique of convenience sampling with the Slovin formula so that a sample of 302 respondents was obtained. The analytical technique used is Structural Equation Modeling (SEM). The results showed that product quality had an effect on purchasing decisions. In addition, the suitability of the price with the benefits and quality received by consumers will be very sensitive in responding to the level of pricing applied to the product.